Evaluation of the growth of Rhizobium leguminous forest tree on different culture media - Souza, Luiz Augusto Gomes de; Magalhães, Fátima Maria Moreira; Oliveira, Luiz Antonio de (Pesquisa Agropecuaria Brasileira, 2014)
Rhizobium isolations from leguminous forest tree nodules in conventional manitol medium (YMA) pH 6.8, carried out at the INPA laboratory, have frequently been unsuccessful. In this study, media with different pH levels and/or carbon sources (xilose (YXA) pH 5.0, YXA pH 7.0, manitol (YXA) pH 5.0, YMA pH 7.0) were evaluated as substrates for Rhizobium isolations from 17 tropical leguminous tree species. Rhizobium strains were isolated from all nodules tested, but depending on nodule procedence, isolates were obtained only in certain media. For the majority of noduIes tested, Rhizobium isolation was only possible in media with pH 5.0. In relation to the carbon source, there were no differences, e.g., the same number of isolates were obtained in both carbon sources tested. The results suggest that genetic variability for pH preference occurs in Rhizobium populations in "terra-firme" Amazonian forest and that studies about these associations must consider the isolation media.